1996
DOI: 10.1093/infdis/174.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Tyrosine Kinase Inhibitors on Tumor Necrosis Factor and Nitric Oxide Production by Murine Macrophages

Abstract: The temporal requirements for tyrosine phosphorylation in the induction of tumor necrosis factor (TNF) and inducible nitric oxide synthase (NOS) were compared in the routine macrophage cell line RAW 264.7. Preincubation of RAW 264.7 cells with herbimycin A or genistein (but not with either of three tyrphostins tested) significantly blocked TNF and NOS production on exposure of these cells to combinations of lipopolysaccharide (LPS) and interferon-gamma (IFN-gamma). The addition of either genistein or herbimyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
8
20
0
2
Order By: Relevance
“…Their activation is crucial to the progression of multiple inflammatory diseases such as septic shock, chronic inflammation, and atherosclerosis, via the release of inflammatory and cytotoxic mediators like cytokines or NO (Tamir and Tannenbaum 1996). In the present study, we have shown that exposing macrophages to LPS and IFN-c simultaneously induces a synergistic effect in terms of NO production as well as TNF-a secretion, in accordance with other authors (Orlicek et al 1996).…”
Section: Resultssupporting
confidence: 92%
“…Their activation is crucial to the progression of multiple inflammatory diseases such as septic shock, chronic inflammation, and atherosclerosis, via the release of inflammatory and cytotoxic mediators like cytokines or NO (Tamir and Tannenbaum 1996). In the present study, we have shown that exposing macrophages to LPS and IFN-c simultaneously induces a synergistic effect in terms of NO production as well as TNF-a secretion, in accordance with other authors (Orlicek et al 1996).…”
Section: Resultssupporting
confidence: 92%
“…We showed here that addition of PGE 2 to the cocultures of mycoplasma-infected YAC-1 cells and macrophages significantly decreased TNF production but has no effect on NO release nor on YAC-1 cell cytotoxicity. These results suggest that mycoplasma-induced TNF and NO production are differentially regulated and corroborate the view that different pathways are involved in generation of these two molecules as suggested by Zhang and Morrison [29] and Orlicek et al [30]. The mechanisms involved in NO and TNF induction by mycoplasmas are poorly understood.…”
Section: Discussionsupporting
confidence: 89%
“…LPS alone is a weak stimulus for iNOS production by RAW 264.7 cells unless very high concentrations (e.g., Ն100 ng/mL) of LPS are used [12,15]. rIFN-␥ alone triggers iNOS accumulation by these cells in a dose-dependent fashion, but combinations of LPS and rIFN-␥ lead to synergistic accumulation of iNOS mRNA and protein [12,15].…”
Section: Murine Macrophagesmentioning
confidence: 99%
“…LPS alone is also a potent stimulus for TNF production, whereas rIFN-␥ alone stimulates relatively small amounts of TNF secretion by these cells [12,15].…”
Section: Murine Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation